2012
DOI: 10.3126/ajms.v2i3.4222
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and antimicrobial properties of the methanolic extracts of <i>Bombax buonopozense</i> leaf and root

Abstract: Objective: The leaf and root of Bombax buonopozense which have some ethnomedicinal applications were subjected to phytochemical screening and antimicrobial activity against some disease causing microorganisms. Material & Methods:The phytochemical composition was evaluated using standard procedures. Susceptibility of these clinical isolates (Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumonae, Proteus spp. and Escherichia coli) to the extracts was determined using the agar diffusion method.Results: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The yield was 9.84% w/w semi-solid light green powder. The dried extract was stored in airtight sterile containers in a refrigerator until the experimental period (22).…”
Section: Preparation Of Leaf Extractmentioning
confidence: 99%
“…The yield was 9.84% w/w semi-solid light green powder. The dried extract was stored in airtight sterile containers in a refrigerator until the experimental period (22).…”
Section: Preparation Of Leaf Extractmentioning
confidence: 99%
“…These compounds have been found to have termiticidal effect against subterranean termite, Copototerrmespormosanus Shiraki. Akuodor, et al (2012), have extracted phytochemicals such as alkaloids, flavonoids, tannins, saponins, terpenoids, steroids, phlobatannins, anthraquinones from roots and leaves of Neen. These have been reported to antibacterial, antifungal, and antioxidant properties.…”
Section: Weight Lossmentioning
confidence: 99%
“…Different parts of the plant are used for different purposes (Dubost, 1984). The leaf, stem bark and root have been reported to possess antiplasmodial, antidiarrhoeal, pains, fever and anti-ulcer activities (Akuodor et al, 2011f;Akuodor et al, 2011g;Iwuanyanwu et al, 2012;Akuodor, 2011h;Nwagba et al, 2013). Earlier studies also have reported its nutritive and antimicrobial properties (Mann et al, 2003;Akuodor et al, 2011c;Mann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%